Penggunaan penyepadanan imej berdasarkan kawasan dalam fotogrametri jarak dekat bagi pengukuran permukaan struktur - Sahdan, Ahmad Yusof (2006)
In civil engineering, web deformations of a structure, in particular steel, are useful indicators pertaining to its failure. Present laboratory methods employed in determining the web deformations are through the use of LVDT. This method are difficult were many points needed to be measured before plotting of the web profile. Measurement may be cannot done because the positions of structure is high or no assessment. This thesis presents the use of close range digital photogrammetry to obtain a three-dimensional model of a deformation web structure’s. Since, photogrammetry has always had the advantage of being able to provide measurements on a large number of points on the object of interest, the representation of the surface deformations would be better. Image correspondence is achieved by using an area-based image matching and centroid matching which makes use of simple surface models. Laboratory tests involving load test on steel Ibeams were performed. Images of the web part under loading were captured using off-the shelf digital cameras that are relatively fixed and calibrated. Whilst the image matching process employs a revised area-based matching algorithm, the image coordinate refinements and the three-dimensional model of the web profile was acquired through elementary photogrammetric operations. Validation of the results was done by means of comparing the photogrammetric output against those obtained from centroid image matching. The results show that the differences between areabased matching and centroid matching approaches are significant which suggest that the former yielded accuracy in the order of 1.5 times better than the latter. This indicates that the use of close-range digital photogrammetry in producing the profile of web deformations is a viable alternative approach to furnish information needed in determining the physical properties of steel structures.